2015
DOI: 10.1186/s13104-015-1357-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices towards rabies: questionnaire survey in rural household heads of Gondar Zuria District, Ethiopia

Abstract: BackgroundRabies is a fatal animal disease of significant public health importance. Domestic dogs are the main reservoir and transmitter of this disease particularly in developing countries. Even though rabies is a highly fatal disease, it is a preventable disease. Community awareness about rabies is one of the key components for prevention. This study describes the knowledge, attitudes and practices of a rural community in Gondar Zuria District, Ethiopia.MethodsA cross sectional study was conducted from March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
68
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 14 publications
22
68
7
Order By: Relevance
“…This misperception is also in agreement with the report of several scholars from different area of Ethiopia (Digafe et al, 2015;Kabeta et al, 2015;Yalemebrat et al, 2016). This misunderstanding about the incubation period indicates that those who believe this incubation period do not seek post exposure prophylaxis once the perceived incubation period passed.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This misperception is also in agreement with the report of several scholars from different area of Ethiopia (Digafe et al, 2015;Kabeta et al, 2015;Yalemebrat et al, 2016). This misunderstanding about the incubation period indicates that those who believe this incubation period do not seek post exposure prophylaxis once the perceived incubation period passed.…”
Section: Discussionsupporting
confidence: 91%
“…All most all (99.3%) had heard about rabies. In line with this finding several scholars from different area of Ethiopia (Digafe et al, 2015;Yalemebrat et al, 2016) and other country (Singh and Choudhary, 2005) reported a similar findings. Regarding the causative agent of rabies 32.7% of respondent were found to have misperception which was starvation and thirst.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations